Imitation simulation of the phase auto-tuning frequency (PAF) system with the extended capture range - Рот, С.М. (Radiotekhnika, 2012)
Spread of the capture band is reached at the cost of changing the structure of the frequency phase autotuning (PAF) system design with additional phase feed-backs (AFB) with the dynamically controlled parameters (DCP) from nonlinear laws. The purpose of the paper consists in estimation of efficiency of the taken technical decisions as to the PAF systems improvement. For this purpose the simulation model of the fast-acting system of PAF synthesizer of frequencies is offered with AFB on the phase with DCP from nonlinear laws with the extended capture band for estimation of its band of capture, studied with the package Simulink of the MATLAB system. The simulated results show that capture band in the system of PAF with two phase modulator as compared to the system of PAF with one phase modulator increased from 5 % to 30 % depending on the initial phase difference of command voltage generator and input signal generator (the filter pass band of the PAF system).